Validation of Enterococcus faecium NRRL B-2354 as a surrogate for Listeria monocytogenes on fresh apples during pilot spray-bar peroxyacetic acid intervention. (January 2021) - Zhu, Mei-Jun; Shen, Xiaoye; Sheng, Lina; Mendoza, Manoella; Hanrahan, Ines
Abstract: Antimicrobial sanitizers applied through a manifold spray-bar brush bed system is a main intervention strategy to prevent cross-contamination of foodborne pathogens on fresh apples. To date, information about antimicrobial efficacy of sanitizers including peroxyacetic acid (PAA) intervention is mainly based on laboratory submerging testing which cannot be directly applied into spray-bar system in apple processing facility due to differences in processing parameters. Previously, we examined anti- Listeria efficacies of PAA in laboratory testing. The studies herein further verified the effectiveness of the selected PAA treatments in a pilot apple spray processing line against Listeria monocytogenes surrogate strains, Enterococcus faecium NRRL B-2354 and Listeria innocua, on apples of the selected varieties. The quality attributes of apples after the selected treatments were further evaluated. A 2-min, 80 ppm PAA treatment at 43 °C and 46 °C resulted in 2.4 and 2.4–2.7 Log10 CFU/apple reduction of E. faecium on different apple varieties, respectively, which had similar reductions compared to L. monocytogenes (2.3–2.5 and 2.5–2.8 Log10 CFU/apple reduction), indicating that E. faecium NRRL B-2354 is a suitable surrogate of L. monocytogenes for evaluating PAA efficacy at test temperatures (22–46 °C). Using this pilot spray-bar system, we further showed that a 30-sec spray wash of 80 ppm PAA at 22 °C and 44–46 °C resulted in 0.8–1.1 and 1.5–1.6 Log10 CFU/apple reduction of E. faecium on apple of the selected varieties, respectively, which were comparable to those of L. innocua . In addition, PAA applied at 44–46 °C did not affect the firmness, total soluble solids content and titratable acidity of apple fruits of tested varieties compared to its application at ambient temperature over 3-week of commercial storage. This study showed that E. faecium NRRL B-2354 is a suitable surrogate strain of L. monocytogenes during the pilot fresh apple processing and provides valuable practical data of PAA spray-bar intervention to the apple industry, facilitating compliance with the Preventive Controls for Human Food Rule. Highlights: PAA was the dominant antimicrobial applied in spray-bar systems of apple packing lines. E. faecium is a suitable surrogate for Listeria on apples during PAA intervention at 22–46 °C. Pilot spray-bar wash of PAA at 80 ppm and 44–46 °C resulted in 1.6 Log10 CFU/apple reduction of Listeria surrogates. Spray wash of PAA at 44–46 °C has no negative impacts on apple fruit quality attributes. Fates of Listeria on apples are similar in different varieties during PAA spray wash at 22–46 °C.